The I-464 Housing Delivery System: A Tool for Urban Modernisation in the Socialist World and Beyond. Issue 2 (4th May 2019) - Erofeev, Nikolay
ABSTRACT: Designed in 1958, the I-464, one of the main Soviet mass housing building systems, was replicated in mass production to accommodate thousands of families. The resulting factories for the production of this prefabricated housing system rapidly disseminated across the most distant regions of the USSR, where their production line was adapted to make the system fit the local climate and seismic conditions. From the early 1960s, the I-464 was exported to foreign countries, including Yugoslavia, Afghanistan, Mongolia, and Cuba. Building upon an analysis of the power distribution between various agents in the command of this system (design, construction institutes and administrative boards), this paper discusses the procedures and practices involved in the design and development of standard blocks, as well as the underlying questions concerning institutional setup. It examines the I-464's development, use in the USSR, and export beyond the socialist world, discussing its specifics in an international context and comparing it with better-known western building analogues.